A Strategy Study on Risk Communication of Pandemic Influenza: A Mental Model Study of College Students in Beijing - Yang H; Pang X; Zheng B; Wang L; Wang Y; Du S; Lu X (Dove Medical Press, 2020)
Honglin Yang,1 Xiaoping Pang,2 Bo Zheng,3 Linxian Wang,4 Yadong Wang,1 Shuai Du,1 Xinyi Lu1 1School of Health Education and Administration, Capital Medical University, Beijing 100069, People’s Republic of China; 2Logistics Department, Da Zhou Centre Hospital, Da Zhou, Si Chuan, 635000, People’s Republic of China; 3Department of Scientific Research, Beijing Children’s Hospital, Capital Medical University, National Center for Children’s Health, Beijing 100045, People’s Republic of China; 4Business School, Cardiff University, Cardiff CF10 3XQ, UKCorrespondence: Honglin Yang Email 407457292@qq.comPurpose: To understand the characteristics of risk perception of influenza pandemic in college students with prominent frequency and the differences between these risk perceptions and professionals. Then, offering a proposal for the government to improve the efficiency of risk communication and health education.Methods: According to the mental model theory, researchers first draw a framework of key risk factors, and then they ask these students about the understanding of the framework with questionnaire and then making concept statistics and content analysis on the respondents’ answers.Results: Researchers find some students’ misunderstanding of pandemic including excessive optimism to the consequences of a pandemic, a lack of detailed understanding of mitigation measures, and negative attitudes towards health education and vaccination. Most students showed incomplete and incorrect views about concepts related to the development and exposure factors, impact and mitigation measures. Once threatened, it may lead to the failure of decision-making. The majority of students we interviewed had positive attitudes towards personal emergency preparedness for a pandemic influenza and specialized health education in the future.Conclusion: Researchers suggest that the government should make a specific pandemic guidance plan by referring to the risk cognitive characteristics of college students shown in the research results, and update the methods of health education to college students.Keywords: risk communication, pandemic influenza, mental model, health emergency, health education